Morphological Variation of Six Pigmented Rice Local Varieties Grown in Organic Rice Field at Sengguruh Village, Kepanjen Subdistrict, Malang District - Shinta, Shinta; Indriyani, Serafinah; Arisoesilaningsih, Endang (Journal of Tropical Life Science, 2014)
Indonesia is the third richest country for pigmented rice source. Morphological character of pigmented rice in Indonesia is less reported since recent publications and descriptions of pigmented rice are only limited to black rice of Cempo Ireng variety and red rice of Aek Sibundong variety. Pigmented rice varieties in Indonesia are cultivated in an organic way. These varieties are Wojalaka black rice of East Nusa Tenggara (NTT), Manggarai of NTT, Toraja of South Sulawesi, Cempo Ireng of Central Java and red rice of Aek Sibundong (leading variety) and Baubau of Southeast Sulawesi. The objective of research was to compare the morphological variation of root, stem, leaf, panicle, floret and the colour of milk mature grain and mature grain by observing the vegetative and generative parts of six local rice varieties. Research had been conducted from February 2012 to February 2014 in Sengguruh Village, Kepanjen District, Malang Regency. This study type was quasi-experiment with eleven replications. Group Random Design was used. The observation was given upon vegetative, reproductive and maturity phases as groups. Independent variables in this research were six rice varieties, while the dependent variable was morphological variation (root, stem, leaf, panicle, floret, milk mature grain and mature grain). The data of morphological variation were tabulated through MS Excel 2007 for windows. Descriptive data analysis was used to determine the average rate and the deviation standard of each variable. Data were analyzed by ANOVA at a cut off value of α of 0.05. It was followed by HSD Tukey Test facilitated by SPSS 16.0. The analysis of multivariate data in cluster and biplot was carried out with PAST. The result of the study indicated that there was morphological difference on stem, leaf, panicle, floret, milk mature grain and mature grain. The colour of the stem in Aek Sibundong variety was purple, while that of other varieties was green. Toraja and Manggarai varieties had the highest height with 163-168 cm, followed by Cempo Ireng with 139 cm, Wojalaka and Baubau with 110-112 cm. Aek Sibundong Variety had the lowest height with 99 cm. Aek Sibundong and Wojalaka varieties had 6-7 internodes which were the greatest number of internode, while other varieties only had 4-5 internodes. Some varieties, such as Aek Sibundong, Wojalaka and Baubau had short and small leaf. The leaflet angle of Aek Sibundong and Baubau were 140 and it might be said as upright, while that of Wojalaka was 430 or moderate. Cempo Ireng, Manggarai and Toraja had its 63-880 of the leaflet angle or it was said as flat. Cempo Ireng and Wojalaka were included into Rice Indica Group while Toraja, Manggarai, Cempo Ireng and Baubau belonged to Rice Javanica Group. There were two morphological groups. Group 1 included Toraja, Manggarai and Cempo Ireng, while Group 2 consisted of Aek Sibundong, Baubau and Wojalaka.